Pendekatan Fenomenologi dalam Studi Agama Konsep, Kritik dan Aplikasi - Rusli Rusli (Islamica: Jurnal Studi Keislaman, 2008)
Phenomenological approach to the study of religion has played such a significant role in unraveling mysteries of religious experiences. By bracketing-out (epoch?), a researcher must suspend all of his/her judgments concerning the phenomenon under investigation in order that he/she may gain the real knowledge of the religious phenomena and experience as well as the essence of a religion. However, this approach has been subjugated to many critiques which show that it is vulnerable on the following areas: the continued philosophical viability of the phenomenology of religion, the surreptitious theological assumptions or motives behind this approach, and the public role of scholar in social community under study.